Penerapan pidana dalam penegakan hukum tindak pidana korupsi pasca putusan Mahkamah Konstitusi - Tri Mahardi; Yanto Yanto (Universitas Janabadra, 2019)
This research is talking about the judgment of Constitution Court of Indonesia Number 25 PUU XIV 2016, its the judgment as an important thing in criminal law enforcement especially toward corruption. The origin of Its judgment come from judicial review toward Article 2 Section 1 and Article 3 Act Number 31 year 1999 juncto Act Number 20 year 2001 about Eradication Corruption Crime. Its judgment push the law official especially the investigator and the judge must be proof the state loss. A state loss must be actual loss, not merely in prediction of state loos or potential loss. This research using normative approach and touched by jurist empirical method, caused by analyzing the act criminal law and comparing with the field practical of criminal justice system. The object of this research is District Attorney of Yogyakarta and Yogyakarta Special Court of Corruption. As law official, the investigator, the general prosecutor and the judge appreciate and obey the judgment, even the investigator, the general prosecutor and the judge appreciate and obey the judgment has been applied its judgment before it. In while on the The judgment of Constitution Court of Indonesia Number 25 PUU XIV 2016 the judge consider that the case is not nebis in idem and also giving legal certainty, because a state loss must be actual.